Propranolol: a new pharmacologic approach to counter retinopathy of prematurity progression - Pascarella, Francesca; Scaramuzzo, Rosa Teresa; Pini, Alessandro; Cammalleri, Maurizio; Bagnoli, Paola; Ciantelli, Massimiliano; Filippi, Luca (Frontiers in Pediatrics, 2024)
Despite the evident progress in neonatal medicine, retinopathy of prematurity (ROP) remains a serious threat to the vision of premature infants, due to a still partial understanding of the mechanisms underlying the development of this disease and the lack of drugs capable of arresting its progression.Although ROP is a multifactorial disease, retinal vascularization is strictly dependent on oxygen concentration. The exposition of the retina of a preterm newborn, still incompletely vascularized, to an atmosphere relatively hyperoxic, as the extrauterine environment, induces the downregulation of proangiogenic factors and therefore the interruption of vascularization (first ischemic phase of ROP). However, over the following weeks, the growing metabolic requirement of this ischemic retina produces a progressive hypoxia that specularly promotes the surge of proangiogenic factors, finally leading to proliferative retinopathy (second proliferative phase of ROP).The demonstration that the noradrenergic system is actively involved in the coupling between hypoxia and the induction of vasculogenesis paved the way for a pharmacologic intervention aimed at counteracting the interaction of noradrenaline with specific receptors and consequently the progression of ROP. A similar trend has been observed in infantile hemangiomas, the most common vascular lesion of childhood induced by pre-existing hypoxia, which shares similar characteristics with ROP. The fact that propranolol, an unselective antagonist of β1/2 adrenoceptors, counteracts the growth of infantile hemangiomas, suggested the idea of testing the efficacy of propranolol in infants with ROP. From preclinical studies, ongoing clinical trials demonstrated that topical administration of propranolol likely represents the optimal approach to reconcile its efficacy and maximum safety. Given the strict relationship between vessels and neurons, recovering retinal vascularization with propranolol may add further efficacy to prevent retinal dysfunction.In conclusion, the strategy of contrasting precociously the progression of the disease appears to be more advantageous than the current wait-and-see therapeutic approach, which instead is mainly focused on avoiding retinal detachment.